2016
DOI: 10.5194/hess-20-4159-2016
|View full text |Cite
|
Sign up to set email alerts
|

Using an integrated hydrological model to estimate the usefulness of meteorological drought indices in a changing climate

Abstract: Abstract. Droughts are serious natural hazards, especially in semi-arid regions. They are also difficult to characterize. Various summary metrics representing the dryness level, denoted drought indices, have been developed to quantify droughts. They typically lump meteorological variables and can thus directly be computed from the outputs of regional climate models in climate-change assessments. While it is generally accepted that drought risks in semi-arid climates will increase in the future, quantifying thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…For instance, Wang et al () investigated the potential impacts of climate change on meteorological, agricultural and hydrological droughts in The Salt Creek Catchment (US) and revealed an increase in drought frequency in the future; Leng et al () conducted the similar study in China and pointed out that droughts will become more extreme and frequent under climate change scenarios. Moreover, von Gunten et al () used drought indices and the HydroGeoSphere hydrological model to project hydrological impacts of droughts in the context of climate change in the Lerma catchment (Spain) and indicated an increase in drought severity in the future. In another study, Kamali et al () assessed meteorological, agricultural and hydrological droughts in the Karkheh River Basin (Iran) using three drought indices and Soil and Water Assessment Tool (SWAT) and found that the frequency of extreme droughts is predicted to increase in the future.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang et al () investigated the potential impacts of climate change on meteorological, agricultural and hydrological droughts in The Salt Creek Catchment (US) and revealed an increase in drought frequency in the future; Leng et al () conducted the similar study in China and pointed out that droughts will become more extreme and frequent under climate change scenarios. Moreover, von Gunten et al () used drought indices and the HydroGeoSphere hydrological model to project hydrological impacts of droughts in the context of climate change in the Lerma catchment (Spain) and indicated an increase in drought severity in the future. In another study, Kamali et al () assessed meteorological, agricultural and hydrological droughts in the Karkheh River Basin (Iran) using three drought indices and Soil and Water Assessment Tool (SWAT) and found that the frequency of extreme droughts is predicted to increase in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Droughts are considered a serious natural hazard, especially in semi-arid regions where devastating and catastrophic damages are recorded [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], and have been mainly categorized (on the basis of duration, impact and recovery rate) into meteorological (defined by a lack of precipitation over a certain period of time for a certain region), agricultural (defined by a period of declining soil moisture and reduced crop yields) and hydrological (defined by a reduced surface and subsurface water availability for a given water resource), and socio-economic drought, expressed to mean "a failure of water resource management to meet the supply and demand of water, taken as an economic good" [16][17][18][19]. The socio-economic definition of drought is a perspective that has not been applied to many studies/analyses of drought found in the literature as it is possibly seen as an outcome/impact of drought rather than a category of drought.…”
Section: Introductionmentioning
confidence: 99%